2008
DOI: 10.1016/j.tins.2008.02.008
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial impairment, oxidative stress and neurodegeneration connection: reality or just an attractive hypothesis?

Abstract: Aging is the most important risk factor for common neurodegenerative disorders such as Parkinson's and Alzheimer's diseases. Aging in the central nervous system has been associated with elevated mutation load in mitochondrial DNA, defects in mitochondrial respiration and increased oxidative damage. These observations support a 'vicious cycle' theory which states that there is a feedback mechanism connecting these events in aging and age-associated neurodegeneration. Despite being an extremely attractive hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
149
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(160 citation statements)
references
References 72 publications
(80 reference statements)
5
149
1
5
Order By: Relevance
“…The description of these results and their impact on the validity and the future of the theory is the main subject of recent reviews in the field [22][23][24][25].…”
Section: Recent Results That Are Incompatible With the Mfrtamentioning
confidence: 99%
“…The description of these results and their impact on the validity and the future of the theory is the main subject of recent reviews in the field [22][23][24][25].…”
Section: Recent Results That Are Incompatible With the Mfrtamentioning
confidence: 99%
“…Nevertheless, if mitochondrial dysfunction is the cause or effect of protein aggregation in PD is still controversial. Some studies showed that complex I inhibition with drugs like rotenone promoted a number of PD symptoms, such as degeneration of substantia nigra neurons, increased ROS and α-synuclein aggregates (reviewed in Fukui andMoraes, 2008 andAndersen, 2011). In addition, the increased α-synuclein oligomerization in PD cybrids through a complex I-mediated mechanism that involves the cystoskeleton disorganization, supported the hypothesis of a mitochondrial dysfunction-induced PD (Esteves et al, 2009).…”
Section: In Parkinson´s Diseasementioning
confidence: 94%
“…Indeed, the role of functional imaging with FDG PET would not be so important if the results of two decades of investigation into the molecular genetics and pathophysiology of brain disorders had not clearly demonstrated that degeneration occurs preferentially at the synaptic level and involves dysfunction in mitochondrial energy metabolism [31][32][33]. For this reason, this technique is nowadays considered the most appropriate approach to track local energetic transformation in the living human brain [34].…”
Section: Baruch Spinozamentioning
confidence: 99%